Active Cell Balancing Approach for Efficient Battery Management System - Sharma, Aakriti; Adhikari, Anusha; Adhikari, Bibek; Pandey, Pratik; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2024)
With the increasing concern for EV and its battery management system, the effective life and performance of li-ion battery is of utmost importance. The battery cells should be frequently equalized in order to increase the lifetime of battery pack. The conventional method of cell balancing is passive cell balancing where excess energy from cell is dissipated in the form of heat until all the cells are equally charged, causing thermal issues and efficiency in the battery pack. This paper proposes a novel approach for improving the efficiency of battery management systems through active cell balancing using the Kalman filter algorithm thereby overcoming the drawbacks of passive cell balancing. The goal of this paper is to develop a system that can extend the lifespan of batteries by ensuring that each cell is charged and discharged evenly. The proposed system includes an active balancing circuit that uses the Kalman filter algorithm to estimate the state of each battery cell and determine the optimal charging and discharging currents.